Health-related quality of life assessment in haemophilia patients on prophylaxis therapy: a systematic review of results from prospective clinical trials - Oladapo, A. O.; Epstein, J. D.; Williams, E.; Ito, D.; Gringeri, A.; Valentino, L. A. (Haemophilia : the official journal of the World Federation of Hemophilia, 2015)
Introduction Prophylaxis is effective in reducing the number of bleeding episodes in patients with severe or moderately severe haemophilia A and B, including those with inhibitors. However, data, predominantly from observational studies, suggest more equivocal effects on health‐related quality of life (HRQoL). Aim To examine the impact of prophylaxis on HRQoL from prospective clinical trials. Methods We performed a systematic literature review of clinical trials evaluating the efficacy of prophylaxis with factor VIII, FIX or bypassing agents. Trials assessing HRQoL via validated instruments were selected and summarized. Results Thirteen trials (haemophilia A [n = 8]; haemophilia B [n = 2]; inhibitors [n = 3]) met all inclusion criteria. HRQoL instruments included the EQ‐5D, SF‐36, Haem‐QoL‐A, Haem‐A‐QoL, Haemo‐QoL and CHO‐KLAT. Improvements in HRQoL following prophylaxis were observed with the EQ‐VAS, SF‐36 and haemophilia‐specific instruments in adult patients and were associated with reduced pain, fewer restrictions in physical activities and better general health. Prophylaxis led to statistically significant or clinically meaningful HRQoL improvement in six trials and non‐significant improvement in four trials; two trials found no improvement and one reported no data. Despite study differences, consistent trends suggested that patients previously treated solely on‐demand and those who experienced marked reductions in the frequency of bleeding with prophylaxis had a greater improvement in HRQoL. Conclusion Contrary to findings of observational studies, the results from the majority of prospective trials using validated instruments showed positive trends for improved HRQoL with prophylaxis in adults.